A Competent MWCNT-Grafted MnOx/Pt Nanoanode for the Direct Formic Acid Fuel Cells - Islam M. Al-Akraa; Moutaz M. Mamdouh; Yaser M. Asal; Ahmad M. Mohammad (Journal of Chemistry)
A novel “MnOx/Pt/MWCNT-GC” nanocatalyst is recommended for the electrooxidation of formic acid (EOFA), the principal anodic reaction in the direct formic acid fuel cells (DFAFCs). The sequential (layer-by-layer) protocol was employed to prepare the catalyst through the electrodeposition of Pt (nano-Pt) and manganese oxide (nano-MnOx) nanoparticles onto the surface of a glassy carbon (GC) electrode supported with multiwalled carbon nanotubes (MWCNTs). The nano-MnOx could successfully mediate the mechanism of EOFA by accelerating the charge transfer, “electronic effect”. On the other hand, MWCNTs could enhance the catalytic performance by changing the surface geometry that inhibited the adsorption of poisoning CO, which is a typical intermediate in the reaction mechanism of EOFA that is responsible for the potential deterioration of the catalytic performance of DFAFCs. Interestingly with this modification, a significant enhancement in the catalytic activity and stability toward EOFA was achieved. Several techniques will be employed to evaluate the catalyst’s morphology, composition, crystal structure, and activity and further to understand the role of each of the nano-MnOx and MWCNTs in the catalytic enhancement.